Pengembangan Kompetensi Sumber Daya Manusia Melalui Pelatihan Fungsional PMG Ahli Secara Online - Tarmana, Dede; Widodo, Widodo (Pusdiklat BMKG, 2020)
Competence development of civil servants can be achieved through trainings and this is among the ASN right that needs to be fulfilled as regulated by the Government Regulation number 11 of 2017. In the implementation of trainings, effectivity and efficiency are necessary to take into consideration. Based on that, the online training is a proper choice by optimazing information technology whenever budget limitation is the concerned matter. The main objective of this paper is to evaluate the effectivity of the Advanced PMG Online Training in increasing participant expertise based on both comprehensive test and assignment. To achieve the paper goal, this study uses some data from 140 participants, including age and gender, field of expertise, value of comprehensive test, and value of assignment. There are three methods used in this study, they are descriptive statistic, proportion analysis and analysis of variance (Anova). Tge results show some characteristics of the training participants , such as the age of the participants ranging between 25 – 29 years, they have equal gender proportion (61 male and 79 female). The effectivity of the training is shown by the percentage of participants who pass the comprehensive test and assignment, with the proportion of 79% participants for the comprehensive test and 100% for the assignment. Statistic test used to to analize the difference between the comprehensive test and assignment value show that the comprehensive test is significally different for the expertise field but not for gender. The highest and lowest average values of comprehensive test are obtained by Climatology field with average value 89.9 and by Meteorology field with average value 71.1, respectively. Meanwhile, the assignment value show significant different for both the expertise field and gender. The highest and lowest values are obatained by Instrumentation Calibration and Cumminication Network field with the average assignment value of 88.3 and by Climatology field with with the average assignment value of 86.1. According to gender,the average assignment value of 88.1 is obtained by female, higher than that of the male of 86.8. These results conclude that the online training is successful to improve the competence of the civil servant/human resources.